(untitled) (Research, Society and Development, 2021)
The use of chemical acaricides is the main method of controlling infestations of ticks in cattle breeding and has been considered responsible for compromising the development of livestock with great economic losses. Turnera subulata Sm. is a plant popularly known in Brazil as chanana, rich in bioflavonoids, a substance which is found in various medicinal plants indicated in folk medicine and tested for their acaricidal properties on Rhipicephalus (Boophilus) microplus. The in vitro bioassay was based on the immersion test of engorged females, in which the dry extract of Turnera subulata Sm. was diluted at steps indecreasing concentrations from 50% to 6,38%. This was performed with wet ticks and immediately dried on absorbent paper, indicating that the tested groups varied in their efficiency percentage of the product. There was no mortality of adult females and the effect of the associated extract with pyrethroid did not show plausible effectiveness, regarding the link between egg hatching rate obtained positive result and there was larvicidal activity, however, the percentages presented in all concentrations are low for ticks controlling. It is suggested further studies with chanana extract associated with other plant products.